2012
DOI: 10.1111/j.1468-1293.2012.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between HIV‐infected and uninfected adults in the contributions of smoking, diabetes and hypertension to acute coronary syndrome: two parallel case–control studies

Abstract: Objectives The aim of the study was to assess the separate contributions of smoking, diabetes and hypertension to acute coronary syndrome (ACS) in HIV‐infected adults relative to uninfected adults. Methods Two parallel case–control studies were carried out. In the first study, HIV‐positive adults diagnosed with ACS between 1997 and 2009 (HIV+/ACS) were matched for age, gender and known duration of HIV infection with HIV‐positive adults without ACS (HIV+/noACS), each individual in the HIV+/ACS group being match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…Findings may also vary over time, as ART for HIV-infected patients has become more lipid-friendly and the incidence of primary MIs in this population has decreased relative to HIV-uninfected individuals [15]. Finally, similar to findings obtained by Calvo-Sanchez et al [28], we found that smoking was a strong predictor of ACS recurrence for HIV-infected but not for HIV-uninfected individuals, highlighting the need for smoking cessation strategies in the HIV-infected patient population. Immunodeficiency has been linked to incident MIs in HIV-infected individuals [9,[29][30][31], including in our own study population [7], an association that may reflect the role of chronic inflammation in the development of atherosclerosis [10].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Findings may also vary over time, as ART for HIV-infected patients has become more lipid-friendly and the incidence of primary MIs in this population has decreased relative to HIV-uninfected individuals [15]. Finally, similar to findings obtained by Calvo-Sanchez et al [28], we found that smoking was a strong predictor of ACS recurrence for HIV-infected but not for HIV-uninfected individuals, highlighting the need for smoking cessation strategies in the HIV-infected patient population. Immunodeficiency has been linked to incident MIs in HIV-infected individuals [9,[29][30][31], including in our own study population [7], an association that may reflect the role of chronic inflammation in the development of atherosclerosis [10].…”
Section: Discussionsupporting
confidence: 67%
“…Finally, similar to findings obtained by Calvo‐Sanchez et al . , we found that smoking was a strong predictor of ACS recurrence for HIV‐infected but not for HIV‐uninfected individuals, highlighting the need for smoking cessation strategies in the HIV‐infected patient population.…”
Section: Discussionmentioning
confidence: 77%
“…Most likely this reflects improved monitoring of lipids and blood pressure in the cohorts rather than any change over time in the risk conferred by these conditions, as well as increased awareness and monitoring of CVD risk and gradual aging of individuals in the cohort, respectively. These findings are consistent with earlier studies [6,15,29,30,31]. The proportion of individuals with an MI who were on ART with a suppressed viral load increased, as did the median CD4 þ cell count.…”
Section: Discussionsupporting
confidence: 82%
“…al. (23) further illustrates these findings. This retrospective chart review utilized two parallel case-controls to evaluate the rate of acute coronary syndrome (ACS) in HIV, with matched populations of HIV-infected patients without ACS, HIV-uninfected patients with ACS, and healthy volunteers.…”
Section: Effectsmentioning
confidence: 58%